2008
DOI: 10.1055/s-2008-1004743
|View full text |Cite
|
Sign up to set email alerts
|

Das postoperative Rezidiv des M. Crohn - Ursachen und Risiken

Abstract: On the basis of defined risk factors, patients with a high risk for recurrence can be identified. This is very important because of the higher risk for complications caused by reoperations compared to primary procedures. That is why interdisciplinary cooperation including postoperative care and optimal conservative treatment are absolutely essential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…This result is significantly different from other reports. In other studies, penetrating behavior was a risk factor for postsurgical recurrence [8, 18-20]. However, Khoury et al [21] reported that stricturing behavior was a risk factor for early reoperation.…”
Section: Discussionmentioning
confidence: 99%
“…This result is significantly different from other reports. In other studies, penetrating behavior was a risk factor for postsurgical recurrence [8, 18-20]. However, Khoury et al [21] reported that stricturing behavior was a risk factor for early reoperation.…”
Section: Discussionmentioning
confidence: 99%
“…Results depend of definition of recurrence. Using, the need for a second resection as the definition for recurrent disease, authors found a recurrence rate of about 20% at 5 years and 35% at 10 years [4,[5][6][7][8][9][10][11][12][13]. In the present study the risk of recurrence was lesser than the previous reports, it was about 7.5%.…”
Section: Discussionmentioning
confidence: 40%
“…A meta‐analysis by Simillis et al [32] described how patients with a penetrating phenotype may have increased postoperative clinical and surgical recurrence rates, although significant heterogeneity among the 13 studies was observed. Higher symptomatic recurrence and earlier reintervention rates in patients with a perforating phenotype have been noted in more recent studies [33, 34].…”
Section: Resultsmentioning
confidence: 84%
“…A consensus exists in the literature regarding tobacco use [35][36][37]120], penetrating (fistulating B1-type) disease [32][33][34], and the presence of specific NOD2/CARD15 mutations [42][43][44][45][46][47][48][49][50]121] as risk factors in postsurgical recurrence. Interestingly, despite the recent advances in our understanding of the genetic basis of CD, the effect of prior family history of CD remains an area in which opposing conclusions have been drawn in the literature to date [28][29][30][31].…”
Section: Factors Predisposing To Recurrencementioning
confidence: 99%